Crime experience and safety perception in gated and non-gated communities in Malaysia : case studies from Kuala Lumpur metropolis - Mohit, Mohammad Abdul; Abdulla, Aishath (2012)
Problem Statement: Property crimes in residential areas has become a concerning issue in Malaysia. Environmental design based crime prevention theories such as defensible space, Crime Prevention through Environmental Design (CPTED) and 2nd generation CPTED have recommended to construct gates and fences as target hardening techniques in the residential areas to prevent crimes. However, this concept has generated several issues, including the safe environment they offer. Approach: Thus, this paper aims at examining the safety perception of the people in gated and guarded neighbourhood vis-â-vis non-gated and guarded neighbourhood. Two low middle income housing communities – a gated and guarded community (GC) and a non-gated and guarded community (NGC) were chosen for the study. Result: Relationship between residents’ crime experiences and perception of safety were studied in both communities and it was found that crime rates are higher in the GC than in the NGC and this indicates that GCs are not safer than NGCs. Conclusion: Based on the findings, the study comes up with several recommendations in order to enhance safety perceptions of low-middle income apartment communities in Kuala Lumpur.